ETNOBOTANI BAHAN KERAJINAN ANYAMAN DARI HASIL HUTAN BUKAN KAYU OLEH MASYARAKAT SEKITAR HUTAN DESA LANDAU GARONG KABUPATEN MELAWI - Saroh, Zummais; Tavita, Gusti Eva; Kartikawati, Siti Masitoh (Universitas Tanjungpura, 2020)
Forest is a stretch of land that contains biological natural resources and has the potential to meet the various needs of human life. One benefit is taken immediately from the forest are non-timber forest products in the form of plants for woven handicraft materials. The utilization of non-timber forest products as woven material in the village of Landau Garong has not been documented. This study aims to record and document non-timber forest products that are used by the community around the forest as raw materials for woven crafts and to know the use of plants as traditional woven materials in the Landau Garong Village Pinoh Selatan District Melawi Regency. The study used a survey method with PRA data collection techniques. Data obtained through observation and interviews. The results showed there were 9 plants species that are used, namely sega rattan (Calamus caesius Blume), jempayang rattan (Plectocomia elongata Martiue ex Blume), tajam rattan (Calamus egregius Burret),Â lingkau bamboo (Gigantochloa hasskarliana), buluh bamboo (Schizostachyum brachycladum),Â kinyel bamboo (Schizostachyum flexuosum), pandanus (Pandanus tectorius), resam (Dicranopteris linearis), coconut leaves (Cocos nucifera). Produces as many as 16 shapes plaits include bakol, semangang, pemansai, ronjong, ragak, bubu, kelongkang, entungap, rojut, lengkak, layan, timpak, capan, ketupat dan kampel.Keywords: Ethnobotany, Woven Craft, Non-Timber Forest Product, Landau Garong Village